Priapism in Sickle Cell Anemia: Emerging Mechanistic Understanding and Better Preventative Strategies. (2nd November 2010) - Crane, Genevieve M.; Bennett, Nelson E.
Abstract : Sickle cell anemia is a common and disabling disorder profoundly affecting mortality as well as quality of life. Up to 35% of men with sickle cell disease are affected by painful, prolonged erections termed ischemic priapism. A priapic episode may result in fibrosis and permanent erectile dysfunction. The severity of sickle cell disease manifestations is variable dependent on a number of contributing genetic factors; however, priapism tends to cluster with other severe vascular complications including pulmonary hypertension, leg ulceration, and overall risk of death. The mechanisms underlying priapism in sickle cell disease have begun to be elucidated including hemolysis-mediated dysregulation of the nitric oxide signaling pathway and dysregulation of adenosine-mediated vasodilation. A better understanding of these mechanisms is leading toward novel preventative strategies. This paper will focus on the mechanisms underlying development of ischemic priapism in sickle cell disease, current acute and preventative treatment strategies, and future directions for improved management of this disorder.